Primary renal sporadic hemangioblastoma: A case report and literature review - Zhang, Jun; Wang, Ning; Chen, Li-Hong; Wang, Wen-Juan; Wang, Mingwen; Liu, Hao; Jiang, Han-Guo; Qi, Yan (Frontiers in Urology, 2022)
Sporadic renal hemangioblastomas (RHBs) are a rare subgroup of extraneurologic hemangioblastomas. They are under-recognized renal tumors whose differential diagnosis remains challenging. Here, we describe a case of RHB in a 61-year-old man was admitted to the hospital two days after the discovery of a right kidney mass. The case of RHB admitted to Department of Pathology, Zhanjiang Central Hospital were studied, and the literatures were reviewed. Immunohistochemistry was used to confirm this tumour. Histologically, the tumor tissue was wrapped by fibrous tissue and composed of tumor cells and a dendritic capillary network. The tumor cells were polygonal, the cytoplasm was eosinophilic or transparent, and the pseudonuclei were enucleated. Immunohistochemically, vimentin, a-inhibin, neurogenic specific enolase (NSE), S-100, smooth muscle actin (SMA), and cluster of differentiation (CD)10 antibodies reacted strongly and were diffused, and Ki-67 was 2% positive. CD31 and CD34 showed vascular morphology. We also summarized related case reports (a total of 41 cases in the Chinese and English literature) to explore the clinicopathological characteristics of RHB and improve the diagnosis and treatment of this disease. RHB is a benign tumor with excellent prognosis, but it is easy to be misdiagnosed as other common renal malignancies. Immunohistochemistry is grealy helpful to its accurate diagnosis.